PENGARUH QUALITY OF WORK LIFE (QWL) DAN BEBAN KERJA TERHADAP KEPUASAN KERJA STAF TELLER BANK PEMBANGUNAN DAERAH KALIMANTAN SELATAN - Gusti Meinar Girda Ariani; Citra Amelia (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This study aims to determine and analyze whether there is influence of, quality of work life and workload to against employee job satisfaciton on Teller Bank Pembangunan Daerah Kalimantan Selatan. This research is categorized as quantitative research with questionnaire instrument. Population in this research is all Teller of Bank Pembangunan Daerah Kalimantan Selatan counted 32 people. Sampling technique by means of saturated sampling technique or census. The data used in this study is the primary dataobtained through questionnaire. The analysis method by using validity test and reliability test using Cronbach Alpha. Measurers proved to be valid and reliable for research instruments. Multiple regression analysis is used to test the hypothesis of this research.based on the results of this study it is known that the results of multiple linear regression test is Y = 23,166 + 0,271 X1 + 0,588 X2 where, quality of work life (X1), workload (X2) and job satisfaction (Y). Then T test results of variable quality of work life has significant affect employee job satisfaction (2,710>2,039). Workload has a significant effect that is (4,922>2,039). Test F together there is a significant influence on employee job satisfaction (247,626 >3,32). R square test results give a value of 0,925 which mean 92,5% employee satisfaction variable can be explained through two independent variables, while the rest of 7,5% influenced or explained by other factors not included in this study.